Anti-inflammatory effects of nesfatin-1 on acetic acid-induced gastric ulcer in rats: involvement of cyclo-oxygenase pathway - (:unkn) unknown (My University, 2017)
In order to elucidate the contribution of cycloxygenase (COX) enzymes in the anti-oxidant and anti-inflammatory mechanisms of nesfatin-1, which improves the healing process of chronic gastric ulcers, either acetic acid (80%; ulcer groups; n = 40) or saline (control groups; n = 40) was applied to the serosal surface of male Sprague Dawley rats' stomachs for 1 min. Both the control and ulcer groups were treated daily with either i.p. saline or nesfatin-1 (0.3 μg/kg; for 3 days). Nesfatin-1-treatment was preceded with i.p. saline, COX-2 inhibitor NS-398 (2 mg/kg), COX-1 inhibitor ketorolac (3 mg/kg) or non-selective COX inhibitor indomethacin (5 mg/kg) for 3 days. The rats were decapitated at the end of the third day, and their trunk blood was collected for the measurements of tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β) and IL-10 using ELISA. The induction of ulcers resulted in increased macroscopic scores, along with elevated gastric malondialdehyde, luminol- and lucigenin-enhanced chemiluminescence levels and myeloperoxidase activity. On the other hand, nesfatin-1 treatment abolished these elevations. Depleted glutathione, superoxide dismutase and catalase activity levels in the saline-treated ulcer group were preserved in the nesfatin-1-treated ulcer group. Increased levels of serum TNF-α, IL-1β, IL-10 in the saline-treated ulcer group, as compared to control group, were significantly decreased in the nesfatin-1-treated ulcer group. The inhibition of COX-1, and/or COX-2 reversed most of the alterations induced with nesfatin-1, but COX-2-blockade was consistently more effective to abolish all nesfatin-1-induced changes. Our results suggest that nesfatin-1 ameliorates ulcer-induced inflammatory response through the modulation of oxidant-antioxidant balance. As selective pharmacological inhibition of COX-1 or COX-2 suppresses the antioxidant/anti-inflammatory effects of nesfatin-1, it appears that nesfatin-1 decreases inflammatory mediators and neutrophil migration by a COX-dependent mechanism, especially by a COX-2- dependent mechanism, during the ulcer healing stage.
Keywords: Animals; Male; Rats; Random Allocation; DNA-Binding Proteins; Dose-Response Relationship, Drug; Rats, Sprague-Dawley; Stomach Ulcer; Acetic Acid; Anti-Inflammatory Agents; Calcium-Binding Proteins; Nerve Tissue Proteins; Nucleobindins; Membrane Proteins; Cyclooxygenase 2; Cyclooxygenase 1